Pertanggungjawaban Pidana Terhadap Pelanggaran Depot Air Minum Berdasarkan Peraturan Undang-Undang Nomor 17 Tahun 2023 - Muhammad Sadam Kulil Janata; Ikhwanul Muslim (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
Legal arrangements regarding drinking water health standards, forms of violations that occur in the field, and law enforcement procedures against business actors who do not fulfill the provisions. This research uses a normative juridical method with an analytical approach to legislation, legal doctrine, and a study of policy implementation practices in the public health sector. The results show that the non-compliance of Refillable Drinking Water Depots with drinking water quality standards both physically, chemically, and micro biologically has the potential to pose a serious risk to consumer health. The Health Law expressly regulates that violations of these provisions can be subject to administrative sanctions in the form of written warnings, fines, and revocation of business licenses, and under certain conditions can be extended to the criminal realm in the form of imprisonment. Law enforcement is carried out through routine supervision by relevant agencies, periodic laboratory testing, and the implementation of a risk management system. In the context of criminal liability, the element of fault (mensrea) is an important requirement that must be proven to be able to ensnare business actors into the criminal realm. The research conclusion emphasizes the importance of strict and consistent application of regulations accompanied by continuous supervision so that the safety of drinking water from refillable drinking water depots is maintained. In addition, education to depot entrepreneurs regarding the obligation to fulfill water quality standards and increasing public awareness of the right to safe, proper and healthy drinking water are preventive strategies that need to be continuously developed in the context of protecting public health.